Burrow systems of mole-rats as refuges for frogs in the Miombo woodlands of south-east Africa. (28th December 2015) - Šklíba, Jan; Jirků, Miloslav; Šumbera, Radim
Abstract: Frogs are known to occasionally utilize the burrow systems of subterranean rodents, but this phenomenon has previously attracted little attention. We recorded frogs in burrows and in/under the molehills of three African mole-rat species (Bathyergidae, Rodentia) during burrow system mapping in Malawi and Zambia during the dry season. Eight frog species were detected. The most abundant of them, Kassina senegalensis, was found in large numbers in active Ansell's mole-rat nest areas, obviously tolerated by the hosts. We speculate that in areas with prolonged dry seasons mole-rats may increase anuran abundances and diversity.